The relationship between stated beliefs and classroom practices of oral corrective feedback. Issue 3 (1st September 2016) - Kamiya, Nobuhiro
Abstract : This study investigated the relationship between stated beliefs of four English as a second language (ESL) teachers about teaching and oral corrective feedback (OCF) and their actual classroom practices. The results show that their stated beliefs of teaching were found to be in accordance with their stated beliefs concerning OCF. While the most inexperienced teacher did not have any concrete ideas about OCF, the other three teachers had established varying degrees of stated beliefs. Nevertheless, they did not consider OCF as a primary tenet of their teaching; other elements were deemed as being more important. Their classroom practices were found to be largely in agreement with their stated beliefs about OCF in the sense that, following their common stated belief of teaching that creating a comfortable environment for students was crucial, they refrained from using explicit correction which could potentially humiliate learners, and instead opted for a more implicit type of OCF, recasts. Despite a general pattern of agreement between teaching statements and practice, one of the most experienced teachers demonstrated incongruent behavior between the two, indicating that teaching experience cannot be exclusively relied upon as an indicator of classroom practice.